Solve ((9xyz)^3)^4 + (a^y)^x: Complex Compound Exponents

Question

((9xyz)3)4+(ay)x= ? ((9xyz)^3)^4+(a^y)^x=\text{ ?}

Video Solution

Solution Steps

00:00 Simplify the following expression
00:03 When there is a power of a power, the combined power is the product of the powers
00:13 Let's use this formula in our exercise
00:20 Multiply the exponents
00:31 When there is a power of a product, all terms are raised to that power
00:41 Let's use this formula in our exercise
00:46 Raise each factor to the power
00:52 This is the solution

Step-by-Step Solution

We'll use the power rule for a power:

(bm)n=bmn (b^m)^n=b^{m\cdot n}

We'll apply this rule to the expression in the problem in two stages:

((9xyz)3)4+(ay)x=(9xyz)34+(ay)x=(9xyz)12+ayx ((9xyz)^3)^4+(a^y)^x= (9xyz)^{3\cdot4}+(a^y)^x=(9xyz)^{12}+a^{yx}

In the first stage, we apply the above rule initially to the first term in the expression and deal with the outer parentheses, then we simplify the expression in the exponent while simultaneously applying the power rule to the second term in the sum in the problem's expression.

We'll continue by recalling the rule for powers that applies to parentheses containing the multiplication of terms:

(wt)n=wntn (w\cdot t)^n=w^n\cdot t^n

We'll apply this rule to the expression we got in the last stage:

(9xyz)12+(ay)x=912x12y12z12+ayx (9xyz)^{12}+(a^y)^x =9^{12} x^{12} y^{12}z^{12}+a^{yx}

We apply the aforementioned power rule to the first term in the sum in the expression we got in the last stage, and apply the power on the parentheses to each of the multiplication terms inside the parentheses.

Let's summarize the solution steps so far:

((9xyz)3)4+(ay)x=(9xyz)12+ayx=912x12y12z12+ayx ((9xyz)^3)^4+(a^y)^x=(9xyz)^{12}+a^{yx} =9^{12} x^{12} y^{12} z^{12}+a^{yx}

Therefore the correct answer is answer D.

Answer

912x12y12z12+ayx 9^{12}x^{12}y^{12}z^{12}+a^{yx}